Preoperative thoracic paravertebral block provides greater benefits for body temperature protection in patients undergoing thoracoscopic lung surgery: a retrospective cohort study - Yue Li; Weixin Zhang; Hansheng Liang; Liang Sun; Xinyue Gao; Yi Feng (BMC Anesthesiology)
Abstract Background Perioperative hypothermia can lead to a variety of adverse events that hinder rapid recovery after surgery in clinical settings. General anesthesia combined with paravertebral block (PVB) may add additional heat loss and thus increase the incidence of hypothermia in patients undergoing thoracoscopic lung surgery. However, gaps in the knowledge of the influence of the PVB time sequence on patients’ body temperature remain. The aim of this study was to explore the potential impact of the time sequence of PVB on the risk of hypothermia. Methods Patients aged 18–85 years who underwent thoracic PVB (TPVB) and thoracoscopic lung surgery at a tertiary hospital were retrospectively included. All the patients were divided into a pre-PVB group and a post-PVB group on the basis of the time sequence of PVB. The demographic, anesthesia-related and surgery-related data of the patients were collected. Propensity score matching was applied, and outcomes were compared between the two groups. The primary outcome was the incidence of hypothermia in the postanaesthesia care unit (PACU). The secondary outcomes included the occurrence of chill and delayed awakening, the numeric rating scale (NRS) score, extubation time and length of stay (LOS) in the PACU. Results A total of 1001 patients were enrolled, with 746 patients in the pre-PVB group and 255 patients in the post-PVB group. After 1:1 propensity score matching, 222 patients were included in each group. The results revealed that body temperature was significantly different between the two groups (pre-PVB group, 36.1 [36.0–36.2]°C; post-PVB group, 36.0 [36.0–36.2]°C; P = 0.012), and the incidence of hypothermia was greater in the post-PVB group than that in the pre-PVB group (24.8% vs. 16.7%, P = 0.047). The NRS scores in the PACU were higher in the pre-PVB group (0 [0–1] vs. 0 [0–0], P = 0.041). There was no statistically significant difference in the other outcomes between the two groups. Conclusions Preoperative TPVB offers more benefits for body temperature protection in patients undergoing thoracoscopic lung surgery, but it slightly offsets the analgesic efficacy in the PACU.